Longitudinal Screening Detects Cognitive Stability and Behavioral Deterioration in ALS Patients - Susan Woolley; Ray Goetz; Pam Factor-Litvak; Jennifer Murphy; Jonathan Hupf; Catherine Lomen-Hoerth; Howard Andrews; Daragh Heitzman; Richard Bedlack; Jonathan Katz; Richard Barohn; Eric Sorenson; et al. (Behavioural Neurology)
Objective. To evaluate longitudinal cognitive/behavioral change over 12 months in participants enrolled in the ALS Multicenter Cohort Study of Oxidative Stress (ALS COSMOS). Methods. We analyzed data from 294 ALS participants, 134 of whom were studied serially. Change over time was evaluated controlling for age, sex, symptom duration, education, race, and ethnicity. Using multiple regression, we evaluated associations among decline in ALS Functional Rating Scale-Revised (ALSFRS-R) scores, forced vital capacity (FVC), and cognitive/behavioral changes. Change in cognitive/behavioral subgroups was assessed using one-way analyses of covariance. Results. Participants with follow-up data had fewer baseline behavior problems compared to patients without follow-up data. We found significant worsening of behavior (ALS Cognitive Behavioral Screen (ALS CBS) behavioral scale, p<0.001; Frontal Behavioral Inventory-ALS (FBI-ALS) disinhibition subscale, p=0.044). Item analysis suggested change in frustration tolerance, insight, mental rigidity, and interests (p<0.05). Changes in ALSFRS-R correlated with the ALS CBS. Worsening disinhibition (FBI-ALS) did not correlate with ALSFRS-R, FVC, or disease duration. Conclusion. We did not detect cognitive change. Behavioral change was detected, and increased disinhibition was found among patients with abnormal baseline behavioral scores. Disinhibition changes did not correlate with disease duration or progression. Baseline behavioral problems were associated with advanced, rapidly progressive disease and study attrition.